PBL-Based LKPD Development to Improve Students' Critical Thinking Skills in Business Economics Subjects at Vocational Schools - Mariana, Mariana; Gimin, Gimin; Kartikowati, Sri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
The weak critical thinking skills of students today encourage educators to seek other ways to attract students' interest in learning. One solution is to develop PBL-based LKPD. Therefore, the present study aims to (1) develop PBL-based LKPD, (2) analyze the effectiveness of the developed PBL-based LKPD, and (3) determine the practicality of PBL-based LKPD. This study is a Research and Development (R&D) research using the 4D model (Define, Design, and Disseminate). The effectiveness of the LKPD, which was developed based on the independent sample t-test test, obtained a sig. value 0.001 < 0.05, which means that there is a significant difference between the test results of the experimental class students and the test results of the control class students. Furthermore, based on the N-Gain score test results in the experimental class using PBL-based LKPD, there was 0.71 with high criteria while the control class using conventional LKPD obtained 0.30 results with low criteria. The practicality of the LKPD developed was assessed based on the teacher's response with an average percentage score of 90% in the very practical category and student responses with an average percentage score of 88.48% in the very practical category. Hence, the use of LKPD is considered effective in improving students' critical thinking skills.